2011
DOI: 10.3851/imp1990
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Urinary Biomarkers of Vascular and Endothelial Function in HIV-Infected Persons Receiving Antiretroviral Therapy

Abstract: Background Cardiovascular disease (CVD) risk can be underestimated in HIV-infected patients receiving antiretroviral therapy (ART). Novel CVD risk markers in this population are needed. We hypothesized that eicosanoid metabolite production is increased with metabolic complications of ART. Our objective was to determine relationships between urine eicosanoids and traditional CVD risk factors in a cohort of HIV-infected persons receiving ART. Methods Cross-sectional analysis of 107 individuals from a prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…32 Virologically suppressed HIV-infected women had urinary levels of eicosanoids consistent with a higher cardiovascular risk profile compared with virologically suppressed HIV-infected men. 33 HIV-infected women may also be at higher risk of stroke. In the Partners HIV cohort, the association between HIV and ischemic stroke was driven largely by women, with an adjusted IRR of 1.76 (95% CI 1.24-2.52) for women compared with 1.05 (95% CI 0.84-1.32) for men.…”
Section: Cardiovascular and Ischemic Stroke Risk In Hiv-infected Womenmentioning
confidence: 99%
“…32 Virologically suppressed HIV-infected women had urinary levels of eicosanoids consistent with a higher cardiovascular risk profile compared with virologically suppressed HIV-infected men. 33 HIV-infected women may also be at higher risk of stroke. In the Partners HIV cohort, the association between HIV and ischemic stroke was driven largely by women, with an adjusted IRR of 1.76 (95% CI 1.24-2.52) for women compared with 1.05 (95% CI 0.84-1.32) for men.…”
Section: Cardiovascular and Ischemic Stroke Risk In Hiv-infected Womenmentioning
confidence: 99%
“…[41] This profile is similar to smokers and persons with higher BMI, despite having a low Framingham risk score. Several studies in HIV-uninfected persons demonstrated similar trends,[4244] but contrasting results exist.…”
Section: Discussionmentioning
confidence: 79%
“…Heavy smokers in our study also had significantly higher F 2 -IsoP, consistent with data in HIV-negative populations 36 and other studies in HIV-infected populations. 11 However, women were less likely than men to be on ART, less likely to report heavy smoking, and adjusted models included both of these covariates. Thus, the relationship between sex and F 2 -IsoP was independent of ART and smoking status.…”
Section: Discussionmentioning
confidence: 99%
“…11 Both studies found that female sex was independently associated with higher F 2 -IsoP levels, an association also seen in HIV-uninfected populations. 12,13 Determining factors that explain higher F 2 -IsoP levels in HIV-infected women compared to men could lead to a better understanding of unique risks for HIV-infected women and provide guidance in management of these patients.…”
Section: Introductionmentioning
confidence: 91%